A deconstructionist reading of William Blake's A Poison Tree - Davood Mashhadi Heidar,; Davoud Reza Zamzia, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper aims to have a deconstructionist reading of William Blake's "A Poison Tree." Highly associated with the well-known poststructuralist Jacques Derrida in the late 1960s, deconstruction's primary concern is "the otherness" and "indeterminacy" or "instability" of the ultimate meaning of the text. A deconstructionist reader tries to bring out elements of marginality, supplementarity, and "undecidability" in the reading of texts. Involved in reading the text very closely and critically, a typical deconstructionist tries to recognize how the text differs from what it (its writer) tends to express. Accordingly, the present study sets out to read and analyse William Blake's "A Poison Tree" to discover if the poem, as deconstructionists assert, might include inconsistencies and contradictory points making the meaning of the text "undecidable" and beyond reach. Methodologically, the present study makes an attempt to show how the text is undermining its own philosophy and logic – that is – to demonstrate how the text subverts and differs from what it appears to communicate. At the end it might be concluded that language can be used as an effective means by its user(s) (speakers/writers) to get power, and suppress or marginalize others. It is also demonstrated how texts seem to include contradictory elements- that is – they differ from what they intend to express. All these argumentations can bring us to "indeterminacy" and "instability" of meaning within the text.